2010
DOI: 10.1143/apex.3.021002
|View full text |Cite
|
Sign up to set email alerts
|

Weak Carrier/Exciton Localization in InGaN Quantum Wells for Green Laser Diodes Fabricated on Semi-Polar {20\bar21} GaN Substrates

Abstract: Carrier/exciton localization in InGaN quantum wells (QWs) for green laser diodes fabricated on semi-polar {2021} GaN substrates is assessed using time-resolved photoluminescence (TRPL) spectroscopy. The estimated characteristic energy, which represents the localization depth in a {2021} InGaN QW, is 15.1 meV. This value is much smaller than that reported for c-plane green InGaN QWs, indicating a high compositional homogeneity of {2021} InGaN QWs and consequently suggesting that the GaN semi-polar {2021} plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
(22 reference statements)
2
47
0
1
Order By: Relevance
“…examined by TRPL measurements. The short radiative lifetime is an indication that the piezoelectric fields are significantly weaker for this plane [31].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…examined by TRPL measurements. The short radiative lifetime is an indication that the piezoelectric fields are significantly weaker for this plane [31].…”
Section: Resultsmentioning
confidence: 94%
“…This result indicates that InGaN QWs on f2 0 2 1g planes exhibit high homogeneity of In concentration even at green region, which give rise to small and stable band tail states even when the QW thickness increases. Recently, Funato et al [31], in collaboration with our group, conducted time-resolved photoluminescence (TRPL) measurements to confirm the homogeneity of InGaN single QWs (SQWs) on f2 0 2 1g planes. TRPL measurements revealed that the localization energy is 15.1 meV, which is only one third of the green InGaN QWs on the c-plane, and is consistent with the homogeneous microscopic PL image and very narrow FWHM of EL peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Such a systematic study on ð11 22Þ semipolar InGaN/GaN MQW with high indium content has not yet been reported, even on very expensive free-standing semipolar GaN substrates. [9][10][11][12][13][14]21 The ð11 22Þ semi-polar GaN has been obtained by overgrowth on nanorod templates, which were fabricated using our self-organized nickel nano-mask technique. 6,7 Four samples, each with five periods of InGaN/GaN MQWs were grown on the overgrown ð11 22Þ GaN.…”
mentioning
confidence: 99%
“…This has also been observed on InGaN/GaN MQWs grown on free-standing GaN substrates. [9][10][11][12][13] A standard two exponential component model is used to study excitonic dynamics, and thus TRPL traces [I(t)] can be described by [16][17][18] IðtÞ ¼ A 1 expðÀt=s 1 Þ þ A 2 expðÀt=s 2 Þ:…”
mentioning
confidence: 99%
“…13 Therefore, Fi g. 1 suggests a smaller potential fluctuation and the consequent weak energetic localization in the (1122) QW, similar to semipolar (2021) QWs. 13,14 However, the PL line width of the (1122) QW (∼175 meV) is larger than that of the (0001) QW (70 meV), which seemingly conflicts with Fig. 1.…”
Section: Ingan Semipolar (1122) Qwsmentioning
confidence: 81%